Contemporary research in brand management - Shaari, Hasnizam; Md. Salleh, Salniza (UUM Press, 2018)
This book is about research in brand management and contemporary issues in marketing. It is designed to bring todays professionals, managers, academicians and students the current research findings relating to issues in branding and marketing across the globe. Generally, branding has been accepted as an important strategy in managing business and marketing activities.This is because effective branding and marketing strategies can help improve business performance and bring up companies to a better position.Hence, this book is a good reference to those who wanted to understand factors influencing product and service brand performance, issues on brand loyalty, consumer purchase intention and Islamic retailing.